GAMBARAN KARAKTERISTIK PASANGAN USIA SUBUR YANG TIDAK MENGIKUTI PROGRAM KB DI WILAYAH KERJA PUSKESMAS BLANG BINTANG KABUPATEN ACEH BESAR - Yusrika Yusrika; Nurul Sakdah; Raisah Raisah (Jurnal Sains Riset, 2020)
The population growth rate continues to soar, the government's efforts to reduce the rate of growth are through the family planning program. Family planning is an attempt to measure the number of children and the desired birth spacing of children, but the unmed net rate in couples of childbearing age is also high, reaching 11% with 4% for thinning and 7% for restriction. This figure has increased compared to the previous survey, which was 8.6%.4 The high number of unmet need for family planning has an effect on the density of birth spacing and the number of children born so that there is a high risk of maternal and infant mortality. The purpose of this study was to describe the characteristics of couples of childbearing age who did not participate in the family planning program in the Work Area of the Blang Bintang Health Center, Aceh Besar District in 2021. This study was descriptive in nature, the research was carried out in the Blang Bintang Public Health Center Work Area, Aceh Besar District, on the 4th to the 9th. January 2021 2020. The population in this study were all couples of childbearing age (especially wives) who did not take part in the familyplanning program, with a sample of 90 people using purposive sampling technique. The results showed that most of the respondents' knowledge about family planning programs were in the sufficient category as many as 56 people (62.2%), most of the respondents' education were in the intermediate category as many as 44 people (48.9%), most of the respondents' income were in the middle category. low as many as 48 people (53.3%). It is hoped that at the Blang Bintang Health Center, Aceh Besar District, it is hoped that this research will be taken into consideration in making policies to improve midwifery care services for mothers, especially family planning so that optimal health status is achieved to improve family welfare.Keywords: Knowledge, Education, Income